A new method to sample DNA from feral honey bee hives in trees. Issue 1 (2nd January 2019) - Williamson, Elisabeth; Groom, Scott; Hogendoorn, Katja
ABSTRACT: Unmanaged, or feral, honey bees can be abundant in Australian agricultural landscapes and provide substantial, but unquantified, crop pollination services. This makes these production systems vulnerable to ecological disturbances. Quantifying the densities of feral honey bees is key to determining the reliance of free pollination services and system vulnerability. Current methods for estimating densities of feral honey bee hives are based on the number of haplotypes identified from drones caught using a pheromone lure. This method assumes that all hives contribute to the drone population, and that the area over which they are attracted is known. To test these assumptions the estimates based on drone capture should be compared to the genetic composition of hives in the same area. We developed a flag and pole method to sample worker sting DNA from feral hives in trees. We show that the use of alarm pheromone isopentyl acetate can significantly increase the efficiency of this method. We also demonstrate that the DNA collected from sting samples will amplify via PCR to a band intensity similar to that of leg tissue. In addition to providing a method to verify hive density estimates based on drone captures other applications of our method are discussed.